The impact of polycyclic aromatic hydrocarbons and fine particles on pregnancy outcome - Dejmek, J; Solanský, I; Benes, I; Lenícek, J; Srám, R J (Environmental health perspectives, 2000)
The relationship between intrauterine growth retardation (IUGR) and exposure to particulate matter [less than/equal to] 10 microm (PM(10)) and particulate matter [less than and equal to] 2.5 microm (PM(2.5))( )in early pregnancy was recently studied in the highly polluted district of Teplice (Northern Bohemia). From this observation rose the question about the possible role of the carcinogenic fraction of polycyclic aromatic hydrocarbons (c-PAHs), which are usually bound to fine particles. The impact of c-PAHs and fine particles on IUGR was analyzed in Teplice and in Prachatice, a region with similarly high c-PAH but low particle levels. All European, single live births occurring in a 4-year period in Teplice (n = 3,378) and Prachatice (n = 1,505) were included. Detailed personal data were obtained via questionnaires and medical records. Mean PM(10), PM(2.5,) and c-PAHs levels during the 9 gestational months (GM) were estimated for each mother. Adjusted odds ratios (AORs) of IUGR for three levels of c-PAHs (low, medium, and high) and for continuous data were estimated after adjustment for a range of covariates using logistic regression models. In the present 4-year sample from Teplice, previously published results about increasing IUGR risk after exposure to particles in the first GM were fully confirmed, but no such effects were found in Prachatice. The AOR of IUGR for fetuses from Teplice exposed to medium levels of c-PAHs in the first GM was 1.60 [confidence interval (CI), 1.06-2. 15], and to high levels 2.15 (CI, 27-3.63). An exposure-response relationship was established by analyzing the continuous data. For each 10 ng increase of c-PAHs in the first GM, the AOR was 1.22 (CI, 1.07-1.39). About the same relationship was observed in Prachatice in spite of the low particle levels. The results prove that exposure to c-PAHs in early gestation may influence fetal growth. The particulate matter-IUGR association observed earlier may be at least partly explained by the presence of c-PAHs on particle surfaces.
Keywords: látky znečišťující vzduch; Embryonic and Fetal Development; vystavení vlivu životního prostředí; Air Pollutants; těhotenství; Indie; výsledek těhotenství; Environmental Exposure; Adult; polycyklické aromatické uhlovodíky; embryonální a fetální vývoj; Fetal Growth Retardation; velikost částic; ženské pohlaví; Humans; Pregnancy; Epidemiologic Studies; Polycyclic Aromatic Hydrocarbons; Pregnancy Outcome; India; epidemiologické studie; dospělí; Female; Particle Size; lidé; růstová retardace plodu